2021
DOI: 10.1212/cpj.0000000000001100
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Motor Disorder

Abstract: Objective:Essential tremor (ET) is one of the most prevalent movement disorders. Because ET is so common, individuals with other neurological disorders may also have ET. There is evidence, however, that the co-occurrence of ET with Parkinson’s disease (PD) and/or dystonia is not merely a chance co-occurrence. We have observed combinations of these three movement disorders within individuals and across individuals within families containing multiple individuals with ET. This observation has a number of implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…In one such study of 4 kindreds, the heterogeneity of ET and the co-existence of PD, dystonia and other neurologic disorders within and between families was recognized [106]. Similar results have been found in recent reports of families including members with ET, PD, and other mixed movement disorders [112]. One study found a higher rates of a family history of ET in PD patients versus healthy controls (OR 3.64), and even greater in TD-PD patients (OR 4.48) [109].…”
Section: Essential Tremorsupporting
confidence: 83%
“…In one such study of 4 kindreds, the heterogeneity of ET and the co-existence of PD, dystonia and other neurologic disorders within and between families was recognized [106]. Similar results have been found in recent reports of families including members with ET, PD, and other mixed movement disorders [112]. One study found a higher rates of a family history of ET in PD patients versus healthy controls (OR 3.64), and even greater in TD-PD patients (OR 4.48) [109].…”
Section: Essential Tremorsupporting
confidence: 83%